Implementing E-Modules Based on Tana Toraja Local Wisdom to Improve Digital Literacy and Learning Outcomes for Junior High School Students - Sitti Saenab; H. Hasanuddin; Ina Nursafitri (Manunggal Halim Jaya, 2026)
Digital literacy and learning outcomes are essential competencies in supporting students’ understanding and adaptation to technology-based learning environments. However, students still experience difficulties in developing digital literacy skills and achieving optimal learning outcomes in science learning. Therefore, innovative learning media integrating technology and contextual learning are needed to address these challenges. This study aimed to determine the level, improvement, and significance of digital literacy skills and learning outcomes of Grade VII students at UPT SPF SMP Negeri 33 Makassar after implementing Tana Toraja local wisdom-based e-modules on the topic of classification of living things. This study employed a pre-experimental design using One Group Pretest–Posttest Design. The population consisted of 288 students from nine classes, while 28 students from Class VII.A were selected through purposive sampling. Data were collected using a 20-item digital literacy questionnaire and a 20-item learning outcomes test and analyzed using descriptive and inferential statistics. The findings showed moderate improvement in digital literacy skills (N-Gain = 0.40) and learning outcomes (N-Gain = 0.48). Furthermore, the t-test results indicated a significance value of 0.000 (<0.05), demonstrating significant improvement in both variables. These findings suggest that Tana Toraja local wisdom-based e-modules effectively improve students’ digital literacy and learning outcomes.